2020
DOI: 10.6004/jnccn.2019.7378
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Response to Olaparib in a Patient With Recurrent Ovarian Cancer and an Entire BRCA1 Germline Gene Deletion

Abstract: PARP inhibitors are known to be effective in patients with ovarian cancer (OC) and germline mutations in BRCA1 and BRCA2 genes (BRCA mutations). Little is known, however, about any correlation between the deletion size and location of the BRCA mutation and the response to PARP inhibitors. Women with OC commonly undergo genetic testing because the presence of a germline BRCA mutation impacts therapeutic decisions and is important for cancer surveillance in patients and their family members. This report presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…In this way, BRCA1 9–12 exon deletion represents the loss of more than 60% of the gene-coding region, so it would be complex to opt for a mutational reversion resistance mechanism to restore the wild-type allele and thus correlate with the better response and survival. Similar observations have been reported in patients with BRCA LGRs and their response to platinum and PARPi ( Randall et al, 2020 ; Wang et al, 2022 ).…”
Section: Discussionsupporting
confidence: 87%
“…In this way, BRCA1 9–12 exon deletion represents the loss of more than 60% of the gene-coding region, so it would be complex to opt for a mutational reversion resistance mechanism to restore the wild-type allele and thus correlate with the better response and survival. Similar observations have been reported in patients with BRCA LGRs and their response to platinum and PARPi ( Randall et al, 2020 ; Wang et al, 2022 ).…”
Section: Discussionsupporting
confidence: 87%
“…The analysis of tumors exposed to platinum therapy or PARPi revealed instances of the rescue of BRCA1/2 function, which is achieved by the second mutation in the affected gene, and, consequently, by the restoration of BRCA1/2 open reading frame [ 24 , 28 ]. These data are supported by clinical observations of extraordinarily good response in patients with deletion of large fragments of BRCA1/2 genes, i.e., in instances where BRCA1/2 function cannot be restored by the secondary mutation [ 51 , 77 ]. Studies on BRCA1 -mutated ovarian carcinomas demonstrated the persistence of a small fraction of BRCA1-proficient cells even in chemonaive tumors; these cells rapidly repopulate tumor mass during the first weeks of platinum-based therapy thus explaining the phenomenon of inevitable emergence of platinum-resistance [ 78 , 79 ].…”
Section: Acquired Resistance To Brca1/2 -Specifc Therapymentioning
confidence: 53%
“…Figure 4 shows the top 20 approved drugs, and the top 10 are described in detail as follows. Olaparib (Rank 35, BE=-8.7, B09074) is a PARP inhibitor primarily indicated for the treatment of ovarian cancer, but has been useful for pancreatic cancer, advanced solid tumors, and gallbladder cancer [87][88][89][90][91][92] . Etoposide (Rank 56, BE=-8.6, B00773) is for use in combination with other chemotherapeutic agents in the treatment of refractory testicular tumors and as first line treatment in patients with small cell lung cancer.…”
Section: Resultsmentioning
confidence: 99%